The role of diagnostic laparoscopy versus ultrasonography and computerized tomography abdomen for chronic/recurrent right iliac fossa pain - Ahmed, Yaser; Dar, Manzoor Ahmad; R. K., Chrungoo; Gulzar, Uzma (International Surgery Journal, 2018)
Background: Chronic right iliac fossa pain (RIF) is a grey area in surgery. No guidelines are available on the best therapeutic approach. Published data are sparse and limited to small series. Objective of this study was to study the role of diagnostic laparoscopy in chronic / recurrent right iliac fossa pain and to study role of diagnostic laparoscopy versus ultrasonography and computerized tomography abdomen for chronic/recurrent right iliac fossa pain Methods: This study was conducted in fifty patients with a history of right iliac fossa pain for duration of three or more months. Each patient was subjected to USG and CT scan. Their findings were compared with findings of diagnostic laparoscopy. Results: Diagnostic accuracy of USG in detecting chronic appendicitis and intra-abdominal pathology as a cause of chronic/recurrent right iliac fossa pain was 66% with sensitivity 75%, specificity 60% and 46% with sensitivity 39.5%, specificity 85.5%. Diagnostic accuracy of CT in detecting chronic appendicitis and intra-abdominal pathology as a cause of chronic/recurrent right iliac fossa pain was 88% with sensitivity 80%, specificity 93.33% and 46% with sensitivity 41.86%, specificity 71.43%. The accuracy of diagnostic laparoscopy in diagnosing chronic/recurrent Appendicitis was 96% with sensitivity 95%; specificity 96.67%; PPV 95%; NPV 96.67%. The overall accuracy of diagnostic laparoscopy in diagnosing chronic/recurrent right iliac fossa pain was 96% with sensitivity 97.67%; specificity 85.71%; PPV 97.67%; NPV 85.71%. Conclusions: CT is better than USG in diagnosing various intra-abdominal pathologies as causes of chronic/recurrent right iliac fossa pain. More ever, it was evident that diagnostic laparoscopy is even better than the above mentioned modalities.